The possible mechanisms of analgesia produced by microinjection of morphine into the lateral habenula in the acute model of trigeminal pain in rats - Emad Khalilzadeh; Gholamreza Vafaei Saiah (Wolters Kluwer Medknow Publications, 2017)
This study aimed to assess the effect of intra-habenular injection of morphine on acute trigeminal pain in rats. Also here, we examined the involvement of raphe nucleus opioid and 5HT3 receptors on the antinociceptive activity of intra habenular morphine to explore the possibility of existence of descending antinociceptive relay between the habenula and raphe nucleus. The numbers of eye wiping response elicited by applying a drop (40 μL) of NaCl (5 M) solution on the corneal surface were taken as an index of acute trigeminal nociception. Intra habenular microinjection of morphine at a dose of 2 μg was without effect, whereas at doses of 5 and 8 μg significantly produced antinociception. Microinjection of naltrexone (4 μg) and ondansetron (1 μg) into the dorsal raphe nucleus prior to intra-habenular saline did not produce any significant effect on corneal pain perception. Pretreatment of the raphe nucleus with ondansetron but not naltrexone prevented intra habenular morphine (8 μg) induced antinociception. Also, intra habenular injection of lidocaine (2%, 0.5 μL reduced corneal pain response. Moreover, intra-habenular microinjection of L-glutamic acid (1 and 2 μg/site) did not produce any analgesic activity in this model of pain. In conclusion, the present results suggest that the activation of the habenular μ opioid receptor by microinjection of morphine or inhibition of habenular neurons by microinjection of lidocaine produced an analgesic effect in the acute trigeminal model of pain in rats. The analgesic effect of intra habenular morphine was blocked by intra-dorsal raphe injection of serotonin 5-HT3 antagonist.